Improvements to the APBS biomolecular solvation software suite. (24th October 2017) - Jurrus, Elizabeth; Engel, Dave; Star, Keith; Monson, Kyle; Brandi, Juan; Felberg, Lisa E.; Brookes, David H.; Wilson, Leighton; Chen, Jiahui; Liles, Karina; Chun, Minju; Li, Peter; et al.
Abstract: The Adaptive Poisson–Boltzmann Solver (APBS) software was developed to solve the equations of continuum electrostatics for large biomolecular assemblages that have provided impact in the study of a broad range of chemical, biological, and biomedical applications. APBS addresses the three key technology challenges for understanding solvation and electrostatics in biomedical applications: accurate and efficient models for biomolecular solvation and electrostatics, robust and scalable software for applying those theories to biomolecular systems, and mechanisms for sharing and analyzing biomolecular electrostatics data in the scientific community. To address new research applications and advancing computational capabilities, we have continually updated APBS and its suite of accompanying software since its release in 2001. In this article, we discuss the models and capabilities that have recently been implemented within the APBS software package including a Poisson–Boltzmann analytical and a semi‐analytical solver, an optimized boundary element solver, a geometry‐based geometric flow solvation model, a graph theory‐based algorithm for determining p Ka values, and an improved web‐based visualization tool for viewing electrostatics.